Obstetric and Neonatal Outcome in PCOS with Gestational Diabetes Mellitus. - Fatemeh Foroozanfard; Seyed Gholam Abbas Moosavi; Fariba Mansouri; Fatemeh Bazarganipour (Tehran University of Medical Sciences, 2014)
Objective: There are some metabolic similarities between women with gestational diabetes mellitus (GDM) and polycystic ovary syndrome (PCOS); it is still uncertain, however, to what extent coexistence GDM and PCOS affects pregnancy outcome. The present study was designed to determine the obstetric and neonatal outcome in PCOS with GDM. Materials and methods:A case-control study was conducted involving 261 GDM women. Thirty hundred-one cases had PCOS based on Rotterdam criteria and the other thirty hundred cases (control group) were women without PCOS. The subjects in each group were evaluated regarding obstetric and those women whose documentation's were complete entered the study. Results:In present study, women with PCOS and GDM had more than twofold increased odds of preeclampsia (p = 0.003, CI = 1.56-5.01, and OR = 2.8) and PIH (p= 0.04, CI = 1.28-4.5, and OR= 2.4). Maternal PCOS and GDM were also associated with threefold increased odds of neonatal hypoglycemia (p= 0.004, CI= 1.49-6.58, and OR= 3.13). Conclusion:Our finding emphasized that pregnant PCOS patients should be followed carefully for the occurrence of various pregnancy and neonatal complications including hypertension and hypoglycemia. We suggested that these neonates should be given more care regarding hypoglycemia symptoms.